2021
DOI: 10.1038/s41419-021-03393-5
|View full text |Cite
|
Sign up to set email alerts
|

Secreted KIAA1199 promotes the progression of rheumatoid arthritis by mediating hyaluronic acid degradation in an ANXA1-dependent manner

Abstract: In inflamed joints, enhanced hyaluronic acid (HA) degradation is closely related to the pathogenesis of rheumatoid arthritis (RA). KIAA1199 has been identified as a hyaladherin that mediates the intracellular degradation of HA, but its extracellular function remains unclear. In this study, we found that the serum and synovial levels of secreted KIAA1199 (sKIAA1199) and low-molecular-weight HA (LMW-HA, MW < 100 kDa) in RA patients were significantly increased, and the positive correlation between them was sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…Alternatively, CEMIP may function as an adaptor molecule for an unknown hyaluronidase via which it assists in the internalization of intermediate-sized HA into the cell. A further explanation suggests that CEMIP induces the degradation of HA when bound to the ANXA1 protein [ 50 ]. Interestingly, a recent report by Dokoshi et al indicated that CEMIP is the major inducible gene responsible for HA catabolism in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, CEMIP may function as an adaptor molecule for an unknown hyaluronidase via which it assists in the internalization of intermediate-sized HA into the cell. A further explanation suggests that CEMIP induces the degradation of HA when bound to the ANXA1 protein [ 50 ]. Interestingly, a recent report by Dokoshi et al indicated that CEMIP is the major inducible gene responsible for HA catabolism in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration‐inducing and hyaluronan‐binding protein (CEMIP, also known as KIAA1199 and HYBID) specifically binds HA and mediates the depolymerization of HA via the cell membrane‐associated clathrin‐coated pit endocytic pathway. In addition, a recent report suggested that CEMIP may increase HA degradation when associated with ANXA‐1 on cellular membranes 62 . CEMIP is localized on the cytoplasmic membrane and in the cytoplasm.…”
Section: Hyaluronan and Photoagingmentioning
confidence: 98%
“…In addition, a recent report suggested that CEMIP may increase HA degradation when associated with ANXA-1 on cellular membranes. 62 CEMIP is localized on the cytoplasmic membrane and in the cytoplasm.…”
Section: Uv Has Expression Epidermis/dermis/whole Skin Referencesmentioning
confidence: 99%
“…In recent years, HA degrading proteins structurally different from the HYAL family have been identified. The cell migration inducing protein (CEMIP), also known as KIAA1199, and the transmembrane protein 2 (Tmem2) both have been shown to contribute to extracellular degradation of HA in fibroblasts ( 31 34 ). Therefore, the regulation of HA synthesis and degradation regulates to the bioavailability of different HA forms with discrete biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of HMW-HA into smaller fragments starts by the activities of Hyal-2, TMEM2, CEMIP, and reactive oxygen species (ROS) at cell surfaces ( 16 ). The smaller LMW-HA fragments may then be bound and cleared by AMs with further intracellular degradation mediated by Hyal-1 (and possibly CEMIP) and by the activity of exoglycosidases (β-glucuronidase and β-N-acetylhexosaminidase) ( 31 34 , 55 ). The LMW-HA fragments are bioactive polymers with a polydisperse molecular weight distribution in the range of ∼10 4 –10 5 Da ( 56 ).…”
Section: Introductionmentioning
confidence: 99%